2019
DOI: 10.37107/jhas.58
|View full text |Cite
|
Sign up to set email alerts
|

Attitude on Premarital Sex, Marriage and Family Size among Adolescents in Pokhara Valley

Abstract: This is a cross-sectional descriptive study aimed to assess the attitude on premarital sex, marriage and family size among school going adolescents in Pokhara valley in 2006. The study included 400 students carried out from 170 from 8 government schools and 230 from 8 private schools of the classes X, XI, and XII of the Pokhara valley. The self administered questionnaire prepared in Nepali method was applied for collecting information from randomly selected students in each selected school. Out of total, 57.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…[5] A study in Pokhara concluded that boys were more liberal to talk on sexual issues than girls. [18] Literatures talk about the online risks and opportunities, especially those of sexual self-exploration and unwanted sexual solicitation. [7][8] [9] Internet based sexual contents and peer networking affects knowledge, attitude, and practices of young people.…”
Section: Discussionmentioning
confidence: 99%
“…[5] A study in Pokhara concluded that boys were more liberal to talk on sexual issues than girls. [18] Literatures talk about the online risks and opportunities, especially those of sexual self-exploration and unwanted sexual solicitation. [7][8] [9] Internet based sexual contents and peer networking affects knowledge, attitude, and practices of young people.…”
Section: Discussionmentioning
confidence: 99%
“…[7] A similar study conducted in Pokhara Valley of Nepal showed that 41% of the students (which included both boys and girls) did not mind having premarital sex. [8] It has been reported in a study conducted by Jain et al [9] that 22.7% of the participants felt that it was ok to have sex with different people and 39.72% felt premarital sex gives popularity. However, in another study, it was a meagre 6.6% who were in favour of premarital sex with staggering 85.8% were against premarital sex.…”
Section: Discussionmentioning
confidence: 99%